Downstream tests, treatments, and annual direct payments in older men cared for by primary care providers with high or low prostate-specific antigen screening rates using 100 percent Texas U.S. Medicare public insurance claims data: a retrospective cohort study. Issue 1 (December 2015) - Zanwar, Preeti; Lin, Yu-Li; Kuo, Yong-Fang; Goodwin, James
Abstract Background All authorities recommend against prostate specific antigen (PSA) screening in men 75 years and older. However, some primary care physicians (PCPs) continue to have high rates of PSA, with large variation in testing. We assessed the tests, treatments, and payments for prostate cancer care in men aged 75 or older who have PCPs with high or low PSA testing rates. Methods We performed a retrospective cohort study using the 2010 Medicare beneficiaries aged 75 or older in Texas, United States who had no prostate cancer in 2007–2009 and had an identifiable PCP. We first identified high vs. low PSA testing PCPs, and then grouped older men in the two PCP groups. We determined health care visits to any provider and to urologists in office and outpatient settings. We estimated the direct medical payments for prostate cancer care for diagnostics, treatments and visits to providers in 2010–2011 using the generalized gamma model with log link function. Results In multilevel, multivariable analyses, 25.4 % (n = 550) of PCPs had PSA testing rates in men aged 75 or older that were significantly higher than the mean rate of all 2, 169 Texas PCPs; 29.4 % (n = 638) had rates that were significantly lower. In all, 22, 853 vs. 23, 929 older men were cared for by PCPs with high vs. low testing rates. Older men cared for by high PSA rate PCPs were more likely to receive a PSA test (OR 3.64, 95 % CI 3.48–3.80), a biopsy (OR 1.16, 95 % CI 1.02–1.31), an ultrasound (OR 1.19, 95 % CI 1.07–1.32) or any radiation treatment (OR 1.31, 95 % CI 1.03–1.66) than men cared for by low PSA rate PCPs. Men with high PSA rate PCPs were 1.21 (95 % CI 1.05–1.39) times more likely to have such outpatient visits. The average annual adjusted Medicare payments for prostate cancer care was 25.60 higher for patients cared for by PCPs with high PSA test rates. Conclusions Older men seeing PCPs with high rates of PSA testing undergo more testing and treatments for prostate cancer, with higher Medicare insurance payments. Future studies are needed to delineate whether men seeing PCPs with low testing rates likely received PSA tests from other providers.